Not the Function of Eating, but Spontaneous Activity and Energy Expenditure, Reflected in “Restlessness” and a “Drive for Activity” Appear to Be Dysregulated in Anorexia Nervosa: Treatment Implications - Casper, Regina C. (Frontiers in Psychology, 2018)
Anorexia nervosa (AN) is uncommon as a syndrome, despite widespread dieting or voluntary food restriction, especially among female adolescents. This suggests that restriction of caloric intake might not be the only component driving weight loss in AN. Historical observations and experimental evidence from energy expenditure studies and recordings from movement sensors reviewed in this paper reveal that AN is associated with motor activity levels and with an energy output not significantly different from that in normal-weight healthy age-matched controls. By contrast, other conditions of prolonged caloric under-nutrition are typically associated with loss of energy, slowing of movements and a decrease in self-initiated activity and well-being. Several hypotheses can be inferred from the findings: (a) that long term severe caloric restriction fails in downregulating movements and energy expenditure in AN. (b) Clinically and subjectively observable as mental and physical restlessness and continued motor activity, this restless energy, differing in intensity, seems to serve as the permissive factor for and possibly to drive exercise and hyperactivity in AN. (c) Such restless energy and increased arousal, generated sometime in the course of the weight loss process, appear to enhance the person’s self-perception and wellbeing, to heighten proprioception, to intensify body awareness and to improve self-esteem. (d) Restlessness and continued motor activity may constitute a phenotype of AN. The therapeutic value of the concept of an abnormality in the energy regulatory system, likely the result of a host of genetic and epigenetic changes in AN, lies primarily in its heuristic and explanatory power and its potential for disease prevention. Restless energy as a permissive and important component for the development and in the maintenance of AN, does not fundamentally alter treatment, since prolonged food deprivation is the principal causal factor for the development of AN. Re-nutrition within a structured treatment plan, to include individual and family therapy and, if indicated, heat application, remains the most effective symptomatic treatment for AN. Corroboration of the concept of restless activation will require the patient’s cooperation and input to identify and capture more precisely the experiences, sensations, and changes that allow the emaciated patient to remain mobile and active.